FOREIGN COUNTRIES' EXPERIENCE IN ASSESSING THE FINANCIAL STABILITY OF COMMERCIAL BANKS - Sattarova Gulshan Mukhiddinovna (American Journals, 2024)
The article analyzes and studies the experience of foreign countries in assessing the financial stability of commercial banks. In particular, the advanced foreign experience of the USA, Germany, France, Italy, and the Russian Federation in this regard, as well as the opinions and comments of economists, are analyzed.
Keywords: Commercial bank, financial stability of banks, assessment of financial stability, CAMELS, PATROL, ORAP rating systems, assessment of bank risks.